Development of a farmer‐friendly portable color sorter cum grader for tomatoes. (3rd October 2021) - Rajkumar, P.; Abinaya, K.; Deepa, J.; Pandiselvam, R.; Rani, C. Indu; Parveen, S.
Abstract: Tomato ( Solanum lycopersicum ) is a major horticulture crop grown worldwide. The ripened tomatoes are excellent source of antioxidants. On the other hand, the transportation of ripened tomatoes to long distances is a challenging task. However, the unripe tomatoes are opted for long‐distance transportation because of their extended shelf‐life. A sensor was developed with an efficient color sorting program using integrated circuits along with a divergent rolling grader. The developed color sorter cum size grader works on the principle of energetic reflection based on measuring the intensity of light and it comprises feed hopper, chain conveyor, belt conveyor, three color sensor (TCS3200), collecting ducts, inlet hopper, grader, outlet section, and collecting trays. Developed machine was operated by a single‐phase 2 hp motor. The performance of the developed machine was analyzed by measuring capacity, sorting efficiency, overall grading efficiency, and skin damage. Based on the performance evaluation, the maximum sorting efficiency and overall grading efficiency obtained were 94.5% and 94.1, 94.1, and 94.6% for ripe and unripe fruits, respectively. Practical Applications: Tomato is one of the important commodities, fetching highly fluctuating market values. Color sorting and size grading are very much needed at the field level to overcome human drudgery and to enhance the market value. In this context, a portable color sensor cum grader has been developed, which can be used by the farmers/traders to get higher prices in the market. The capacity of newly developed equipment was approximately 40 kg/hr. The cost of operation of color sorting cum grading equipment was Rs. 3/kg of tomatoes.